Effective dismantling of waste printed circuit board assembly with methanesulfonic acid containing hydrogen peroxide. Issue 3 (19th January 2017) - Zhang, Xiaojiao; Guan, Jie; Guo, Yaoguang; Cao, Yonghai; Guo, Jiang; Yuan, Hao; Su, Ruijing; Liang, Bo; Gao, Guilan; Zhou, Yuan; Xu, Jinqiu; Guo, Zhanhu
Abstract : Dismantling of waste printed circuit boards (WPCBs) is of great importance in the recycling chain of electronic wastes (e‐wastes), since there are lots of high‐value components and toxic substances contained in the WPCBs. In this work, effective dismantling was achieved by dissolving the lead‐tin solder into a leachant containing methanesulfonic acid (MSA) and H2 O2 . Different concentrations of H2 O2 and MSA as well as leaching time were investigated. The final optimization experiment scheme was obtained from the simulation with the help of Design‐Expert 8.0.6 software. A leachant containing 3.5 mol/L MSA and 0.5 mol/L H2 O2 with a reaction time of 45 min was regarded as the optimum conditions for the selective desoldering separation of electronic components (ECs) from the WPCBs. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 873–878, 2017